Design, synthesis, evaluation, and molecular docking of ursolic acid derivatives containing a nitrogen heterocycle as anti-inflammatory agents. Issue 10 (1st June 2018) - Wei, Zhi-Yu; Chi, Ke-Qiang; Wang, Ke-Si; Wu, Jie; Liu, Li-Ping; Piao, Hu-Ri
Graphical abstract: In an attempt to develop novel and potent anti-inflammatory agents, four novel series of ursolic acid derivatives containing oxadiazole, triazolone and piperazine moieties were designed, synthesized, and evaluated for anti-inflammatory activity. The cytotoxicity and molecular docking studies of these compounds was also assessed. Highlights: Ursolic acid derivatives containing nitrogen heterocyclic were synthesized. The anti-inflammatory activity and cytotoxicity of compounds were evaluated. Compound 11b is a promising anti-inflammatory agent. All compounds did not exhibit any remarkable cytotoxic activity. The molecular docking studies of 11b was performed. Abstract: Ursolic acid derivatives containing oxadiazole, triazolone, and piperazine moieties were synthesized in an attempt to develop potent anti-inflammatory agents. Structures of the synthesized compounds were elucidated by 1 H NMR, 13 C NMR, and HRMS. Most of the synthesized compounds showed pronounced anti-inflammatory effects at 100 mg/kg. In particular, compound 11b, which displayed the most potent anti-inflammatory activity of all of the compounds prepared, with 69.76% inhibition after intraperitoneal administration, was more potent than the reference drugs indomethacin and ibuprofen. The cytotoxicity of the compounds was also assessed by the 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2- H -tetrazolium bromide (MTT) assay, and no compounds showed any appreciable cytotoxic activity (IC50 >100 μmol/L). Furthermore, molecular docking studies of the synthesized compounds were performed to rationalize the obtained biological results. Overall, the results indicate that compound 11b could be a therapeutic candidate for the treatment of inflammation.